Parting ways ; Playing dead [videorecording] - Lazaro, Cheche (The Probe Team)
A follow-up story of Arlene Alonso, a cancer survivor. It tells of how parting with a love one feels. Movie actors who make a living out of playing corposes tell the Probe Team about their special notes.